Pierre Bourdieu's contemporary sociological methodology and its sustainable impacts on the management models of 21st Century health organizations (Research, Society and Development, 2021)
This study will seek to investigate the applications of Bourdieu's contemporary sociology and its sustainable impacts on the management models of healthcare organizations in the 21st century. The objective of this study will be to apprehend meanings and approaches in the scientific literature on the subject, aiming to contribute with investigations to better use the applications of Pierre Bourdieu's contemporary sociology in organizational management models in health. As a database, master's and doctoral dissertations, books and scientific articles researched on the themes will be consulted, in Capes, Scielo, and others, from the period in which it appears until the current times of the 21st century. In the development of the study, surveys, systematization and analysis of the history of the applicability of contemporary sociology of Bourdieu and its impacts on the management models of health organizations of the 21st century will be carried out, so that at the end of this study, it is possible to formulate proposals of improving the management models used in health organizations in light of the critical analysis of what was produced, focusing on the relationships that discuss Bourdieu's reflexive sociology and the organizational world.